Association of Chronic Kidney Disease With Small Vessel Disease in Patients With Hypertensive Intracerebral Hemorrhage - Tsai, Yuan-Hsiung; Lee, Meng; Lin, Leng-Chieh; Chang, Sheng-Wei; Weng, Hsu-Huei; Yang, Jen-Tsung; Huang, Yen-Chu; Lee, Ming-Hsueh (Frontiers in Neurology, 2018)
Background: Chronic kidney disease (CKD) has been closely associated with hypertension and stroke. Although studies have reported the relationship between CKD and cerebral small vessel disease (SVD), the link between CKD, hypertension, and SVD is uncertain. The aim of this study was to investigate the association between CKD and SVD in patients with strictly hypertensive intracerebral hemorrhage (ICH). Methods: 142 patients with acute hypertensive ICH were enrolled in this study. Magnetic resonance imaging was performed to assess imaging markers for SVD. Patients were categorized into 3 CKD groups based on the degree of kidney dysfunction (GFR in mL/min per 1.73 m2): normal kidney function (GFR ≥ 90), mild kidney disease (60 ≤ GFR < 90), and moderate to severe kidney disease (GFR < 60). Results: The prevalence rate of mild and moderate to severe CKD was 50% and 14.8%, respectively. The stage of CKD was associated with history of chronic hypertension (p = 0.046) as well as the prevalence rate of overall and deep cerebral microbleed (CMB) (p=0.001 and p=0.002, respectively). The stage of CKD was a significant risk factor for deep white matter hyperintensity (WMH) (OR 1.848; 95% CI 1.022-3.343, p = 0.042), overall CMB (OR 2.628; 95% CI 1.462-4.724, p = 0.001), lobar CMB (OR 2.106; 95% CI 1.119-3.963, p = 0.021), and deep CMB (OR 2.237; 95% CI 1.263-3.960, p= 0.006), even after adjustment for confounders. Conclusions: In patients with hypertensive ICH, the prevalence of CKD is high even at the early stage of renal function impairment and is associated with the prevalence of CMB and deep WMH. These results reinforce the notion of a link between hypertensive vasculopathy, renal function impairment, and cerebral SVD.